Methotrexate-Loaded Gelatin and Polyvinyl Alcohol (Gel/PVA) Hydrogel as a pH-Sensitive Matrix - Akhlaq, Muhammad; Azad, Abul Kalam; Ullah, Inam; Nawaz, Asif; Safdar, Muhammad; Bhattacharya, Tanima; Helal Uddin, A.B.M.; Abbas, Syed Atif; Mathews, Allan; Kundu, Sukalyan Kumar; Miret, Mireia Mallandrich; Murthy, H. C. Ananda; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Abstract: The aim was to formulate and evaluate Gel/PVA hydrogels as a pH-sensitive matrix to deliver methotrexate (MTX) to colon. The primed Gel/PVA hydrogels were subjected to evaluation for swelling behavior, diffusion coefficient, sol-gel characteristic and porosity using an acidic (pH 1.2) and phosphate buffer (PBS) (pH 6.8 & pH 7.4) media. Fourier transform infrared spectroscopy (FTIR) and thermal gravimetric analysis (TGA) were performed to evaluate the chemical compatibility of the Gel/PVA hydrogel. The shape alteration and release of Gel/PVA hydrogel was conducted at pH 1.2, pH 6.8 and pH 7.4. The drug release kinetic mechanism was determined using various kinetic equations. The physicochemical evaluation tests and drug release profile results were found to be significant (p < 0.01). However, it was dependent on the polymers’ concentration, the pH of the release media and the amount of the cross-linking agent. Hydrogels containing the maximum amount of gel showed a dynamic equilibrium of 10.09 0.18 and drug release of 93.75 0.13% at pH 1.2. The kinetic models showed the release of MTX from the Gel/PVA hydrogel was non-Fickian.The results confirmed that the newly formed Gel/PVA hydrogels are potential drug delivery systems for a controlled delivery of MTX to the colon.